Himalayan Seismic Activity: A Concise Picture - Paudyal, Harihar (Himalayan Physics, 2012)
The lofty Himalayan Mountains have formed due to continuous thrusting of the Indian plate under Eurasian plate. The incessant northward movement of the Indian plate generated large amount of strain energy at the plate boundaries which is released in form of earthquake frequently. Large numbers of earthquakes occurred in past signifies that the Himalayan region is seismically very active. The b- value for the central Himalayan region is determined as 1.15 which defines the level of seismic activity of a region. The Himalayan Physics Vol. 3, No. 3 2012 Page : 35-37